2017
DOI: 10.46582/jsrm.1302008
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin K Localizes to Equine Bone In Vivo and Inhibits Bone Marrow Stem and Progenitor Cells Differentiation In Vitro

Abstract: Selective inhibition of Cathepsin K (CatK) has a promising therapeutic potential for diseases associated with bone loss and osseous inflammation, such as osteoarthritis, periodontitis, and osteoporosis. In horses, stress-related bone injuries are common and accompanied by bone pain and inflammation resulting in excessive bone resorption and periostitis. VEL-0230 is a highly selective inhibitor of CatK that significantly decreased bone resorption and increased bone formation biomarkers. The goal of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Treating RAW 264.7 cells with RANKL initiates osteoclast differentiation signaling through RANK, thereby inducing the expression of key differentiation-related genes, including c-Fos, NFATc1, OSCAR, DC-STAMP, cathepsin K, and TRAP [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, c-Fos and NFATc1 work synergistically to induce the expression of several key osteoclastogenesis-related genes [ 7 , 8 , 9 , 10 ]. Specifically, NFATc1 is known as a key transcriptional regulator of osteoclasts and is an essential factor for osteoclast differentiation [ 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treating RAW 264.7 cells with RANKL initiates osteoclast differentiation signaling through RANK, thereby inducing the expression of key differentiation-related genes, including c-Fos, NFATc1, OSCAR, DC-STAMP, cathepsin K, and TRAP [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, c-Fos and NFATc1 work synergistically to induce the expression of several key osteoclastogenesis-related genes [ 7 , 8 , 9 , 10 ]. Specifically, NFATc1 is known as a key transcriptional regulator of osteoclasts and is an essential factor for osteoclast differentiation [ 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, c-Fos and NFATc1 work synergistically to induce the expression of several key osteoclastogenesis-related genes [ 7 , 8 , 9 , 10 ]. Specifically, NFATc1 is known as a key transcriptional regulator of osteoclasts and is an essential factor for osteoclast differentiation [ 7 , 8 , 9 , 10 ]. OSCAR is an osteoclast-specific immune receptor that serves as a costimulatory signal essential for RANKL-mediated NFATc1 activation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Random sequencing of expressed sequence tags from cDNA libraries and Ctsk immunostaining indicated that Ctsk is predominantly stained in mature osteoclasts. Moreover, Ctsk is granularly located at a single pole of the osteoclasts ( Drake et al, 1996 ; Hussein et al, 2017 ; Debnath et al, 2018 ). Using the same methodology, Ctsk is moderately expressed in osteoblasts and in some osteocytes underlying the matrix of metaphyseal trabecular femoral heads.…”
Section: Identity Of Ctsk + Cells In the Skeletal ...mentioning
confidence: 99%
“…Using the same methodology, Ctsk is moderately expressed in osteoblasts and in some osteocytes underlying the matrix of metaphyseal trabecular femoral heads. However, the Ctsk expression of the protein was reduced during bone matrix formation ( Mandelin et al, 2006 ; Hussein et al, 2017 ; Lotinun et al, 2019 ). Immunohistochemical analysis conducted in the degradation area, weight-bearing areas of knee cartilage, and menisci in osteoarthritis patients showed that chondrocytes and fibroblast-like synoviocytes expressed Ctsk.…”
Section: Identity Of Ctsk + Cells In the Skeletal ...mentioning
confidence: 99%